A Numerical Modeling for Study Marine Current in the Manado Bay, North Sulawesi - Parabelem Tinno Rompas Dolf; Jenly Dyliep Manongko Isria (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This study is investigating about marine currents provided electrical energy through the numerical model. The objective of this study is to know the power available distributions in the Manado Bay, North Sulawesi, Indonesia. The Manado Bay was width 2200 m with 79 m of depth. In computation, we are made grids in x and y horizontal were 7 m respectively, also for z vertical of four layers. The results shown that the power available distributions in the Manado Bay at 0.1 Sv were 0.00-20.00 kW/m2 when low tide currents and when high tide currents were 0.00-105 kW/m2. The values will enable for marine currents power plant in the Manado Bay to future.